2017
DOI: 10.1016/j.scog.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and preliminary efficacy of remotely delivering cognitive training to people with schizophrenia using tablets

Abstract: BackgroundLimited access to Cognitive Training (CT) for people with schizophrenia (SZ) prevents widespread adoption of this intervention. Delivering CT remotely via tablets may increase accessibility, improve scheduling flexibility, and diminish patient burden.MethodsIn this reanalysis of data from a larger trial of CT, we compared two samples of individuals with SZ who chose to complete 40 h of CT either on desktop computers in the laboratory (N = 33) or remotely via iPads (N = 41). We examined attrition rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…To support users’ engagement and acceptance of technology while solving cognitive exercises, two of them use an applied behavioral economics’ gamification method: Bias Blaster, a bubble-shooting game that uses the Cognitive Bias Modification Interpretation (CBM-I) method (Steel et al, 2010) for training patients to interpret ambiguous social situations in a positive way (Wartena & van Dijk, 2013), and Challenging Our Minds (Mariano et al, 2015), an online cognitive remediation program, provides gaming tasks to improve attention, executive function, memory, visual-spatial abilities, problem-solving and communication. In the third program, Brain HQ (Biagianti et al, 2017), auditory processing training and social cognition exercises aim to improve working memory, processing speed and brain plasticity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To support users’ engagement and acceptance of technology while solving cognitive exercises, two of them use an applied behavioral economics’ gamification method: Bias Blaster, a bubble-shooting game that uses the Cognitive Bias Modification Interpretation (CBM-I) method (Steel et al, 2010) for training patients to interpret ambiguous social situations in a positive way (Wartena & van Dijk, 2013), and Challenging Our Minds (Mariano et al, 2015), an online cognitive remediation program, provides gaming tasks to improve attention, executive function, memory, visual-spatial abilities, problem-solving and communication. In the third program, Brain HQ (Biagianti et al, 2017), auditory processing training and social cognition exercises aim to improve working memory, processing speed and brain plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…BrainHQ (Biagianti et al, 2017) Cognitive training Auditory processing training and social cognition exercises A study with seven participants with schizophrenia + − Users, researchers Significant effects of time on verbal learning (p = .02) and problem-solving (p = .05) on the omnibus test.…”
Section: Tabletmentioning
confidence: 99%
“…While laboratory-based developments aim to enhance cognitive learning, ongoing work in the field aims to enhance the treatment's accessibility and its individuallevel effectiveness in improving both cognition and recovery outcomes. 31,32 Indeed, there is increasing enthusiasm for implementing theoretically and empirically grounded CR approaches in large systems of psychiatric care. However, there is a lack of clarity about a number of factors that impact how CR can be feasibly implemented in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…The partnership model has the potential to reduce the overall cost of training and can be more flexible in terms of scheduling-making the program accessible to more people who need it. This is particularly important, since prior research has revealed scheduling and commuting to multiple cognitive training appointments each week can be burdensome when juggling work, school, and other medical appointments (Biagianti et al, 2017). Encouragingly, a home-based model has been successfully implemented in neurofeedback training programs to reduce costs and improve access to treatment (Kober et al, 2016).…”
mentioning
confidence: 99%